Thinking change and changing thinking - Banister, D; Givoni, M; Macmillen, J; Schwanen, T (Edward Elgar, 2013)
The need, urgency and benefits of moving to low carbon mobility are clear, and amount to more than the need to reduce carbon emissions, or other environmental harms from transport. This has been highlighted throughout the book. The prospects of anthropogenic climate change and the actions required in this respect only reinforce the need for change in the mobility and transport system. This need has been recognized and for some time, but progress towards low carbon mobility has so far been too slow, in places non-existent. It is commonly stated that carbon reductions in transport are difficult and expensive, suggesting other sectors should curtail emissions. This is not acceptable, especially if reductions elsewhere are offset by increased mobility. So far, transport has taken a low profile when it comes to making a substantial contribution to energy and carbon reduction targets and while this has allowed mobility to increase it has not necessarily favoured society. Moving to low carbon mobility, it is argued in the book, is not only about reducing the costs associated with mobility but also about increasing the benefits from mobility to society. It likewise argues that it is not the amount of mobility but its quality and purpose that matter.